How Fast is Your Website? - MEENAN, PATRICK (Communications of the ACM, 2013)
The article discusses website loading speed, covering topics such as website testing techniques, website monitoring software, and web browsers. Browser caches, computer configuration, and Internet bandwidth connectivity are discussed, as well as content distribution networks (CDNs), JavaScript programming language, and the HTML language. Standardized interfaces for web performance reporting, the Navigation Timing specification developed by web browsers, and measurement of Internet user experience are discussed, and charts are presented on topics such as speed indexes, browser performance reporting services, and page load times by geographic region.